2005
DOI: 10.1029/2005gl023112
|View full text |Cite
|
Sign up to set email alerts
|

Thermosteric sea level rise, 1955–2003

Abstract: [1] For the 1955 -2003 period, the thermal expansion of the 0 -700 m layer of the World Ocean contributed approximately 0.33 mm/year to global sea level rise. About half of this thermosteric trend is due to warming of the Atlantic Ocean. Approximately one third of the total thermosteric rise is due to the warming of the Pacific Ocean. For the period of available TOPEX/Poseidon (T/P) satellite altimetry data (1993 -2003), the linear trend of thermosteric sea level (0 -700 m) is 1.23 mm/year, 60% of which is du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
364
3
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(409 citation statements)
references
References 17 publications
35
364
3
1
Order By: Relevance
“…Whereas the volcanic impact on the water cycle is transient, the steric drop in GSL may persist for many years (2,18). We note that the proposed mechanisms are consistent with the observation (see SI) that the initial rise in sea level is especially evident in regions where the steric change is relatively small, such as in the Baltic and Northeast Pacific (19,20). The magnitude of the impact on the water cycle may be seen by comparison with natural changes in global river discharge (21) where a 5% change corresponds to a change in GSL of 5.5 mm/year.…”
Section: Resultssupporting
confidence: 74%
“…Whereas the volcanic impact on the water cycle is transient, the steric drop in GSL may persist for many years (2,18). We note that the proposed mechanisms are consistent with the observation (see SI) that the initial rise in sea level is especially evident in regions where the steric change is relatively small, such as in the Baltic and Northeast Pacific (19,20). The magnitude of the impact on the water cycle may be seen by comparison with natural changes in global river discharge (21) where a 5% change corresponds to a change in GSL of 5.5 mm/year.…”
Section: Resultssupporting
confidence: 74%
“…A recent study by Antonov et al (2005) confirmed that the thermosteric sea level change in the entire equatorial Pacific (15°S-15°N) reveals ENSO-driven inter-annual variability. More locally, high sea surface temperatures are recorded during warm ENSO episodes in the eastern Pacific warm pool ( Fig.…”
Section: Resultsmentioning
confidence: 71%
“…However, regional sea level changes have been very inhomogeneous over this period and are affected by changes in atmospheric wind stresses, and surface heat and freshwater fluxes (Ishii et al, 2003;Volkov et al, 2003;Antonov et al, 2005;Bindoff et al, 2007;Berge-Nguyen et al, 2008;Church et al, 2008;Woodworth et al, 2011a). Hence, regional sea level change is often associated with variations in ocean circulation (Landerer et al, 2007;Levermann et al, 2005;Flückiger et al, 2006;Stammer, 2008;Stammer et al, 2011;Lorbacher et al, 2010;Hu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%